Ethnographies of Archaeological Practice: Cultural Encounters, Material Transformations - Edgeworth, Matt (Rowman & Littlefield Publishers, 2006)
Ethnographic perspectives are often used by archaeologists to study cultures both past and present - but what happens when the ethnographic gaze is turned back onto archaeological practices themselves? That is the question posed by this book, challenging conventional ideas about the relationship between the subject and the object, the observer and the observed, and the explainers and the explained. This book explores the production of archaeological knowledge from a range of ethnographic perspectives. Fieldwork spans large parts of the world, with sites in Turkey, the Netherlands, Mexico, Brazil, Italy, Germany, the USA and the United Kingdom being covered. They focus on excavation, inscription, heritage management, student training, the employment of hired workers and many other aspects of archaeological practice. These experimental ethnographic studies are situated right on the interface of archaeology and anthropology_on the road to a more holistic study of the present and the past.